2009
DOI: 10.1631/jzus.b0820316
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant and hypnotic effects of amiodarone

Abstract: Amiodarone hydrochloride is a potent anti-arrhythmic agent, known as a multiple ion-channel blocker in the heart. Although it has been detected in the rat brain, there are no data related to its central nervous system (CNS) effects. In this study, we evaluated anticonvulsant and hypnotic effects of amiodarone. Convulsions were induced by phentylenetetrazole (PTZ) (100 mg/kg) or caffeine (300 mg/kg) in mice. In both models, amiodarone prolonged both latency period and time to death, and acted as an anticonvulsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…CAT acts as preventive antioxidant [82]; its primary role is to scavenge H 2 O 2 that has been generated by free radicals and convert it to water [83]. The present results showed that the administration of amiodarone and the exposure to waterpipe smoke caused a significant decrease in CAT activity these results are consistent with the previous study of Ozbakis-Dengiz and Bakirci [28]; which demonstrated that administration of amiodarone decreased the activity of CAT in male mice and rats. Also, Al-Shammari et al [52] postulated that the decrement in CAT activity in amiodarone administered group resulting from induction of oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CAT acts as preventive antioxidant [82]; its primary role is to scavenge H 2 O 2 that has been generated by free radicals and convert it to water [83]. The present results showed that the administration of amiodarone and the exposure to waterpipe smoke caused a significant decrease in CAT activity these results are consistent with the previous study of Ozbakis-Dengiz and Bakirci [28]; which demonstrated that administration of amiodarone decreased the activity of CAT in male mice and rats. Also, Al-Shammari et al [52] postulated that the decrement in CAT activity in amiodarone administered group resulting from induction of oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…Wyss et al [27] reported that amiodarone pass into the brain and it has an anticonvulsant and hypnotic effects. Moreover, amiodarone prolonged the sleeping time and behaved as central nervous system depressant drug in pentobarbital-induced sleeping in rat model [28]. Many reports attributed the anticonvulsant activity of amiodarone to its activity as a multiple ion-channel blocker drug which inhibit Na + , Ca 2+ inward and K + outward currents [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemically administered amiodarone passes the blood–brain barrier [ 13 , 14 ] and can exert its pharmacological effects on the central nervous system [ 15 ]. The pharmacological profile of amiodarone is complex.…”
Section: Discussionmentioning
confidence: 99%
“…some antiarrhythmics exhibiting anticonvulsant effects at lower doses may decrease the seizure threshold or even induce seizures at higher doses, e.g. mexiletine [ 5 12 ]. Antiarrhythmics have been found to affect not only a seizure threshold but also the action of antiepileptics in different seizure models [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%